Telework in Public Sector Organizations: The Slovak National Library - Mária Murray Svidroňová; Beáta Mikušová Meričková; Juraj Nemec (Central European Public Administration Review)
Reforms of government and public administration combined with use of information and communications technologies (ICT) have brought many innovations in public sector, including telework as a form of organizing and performing work out of the employers´ premises. This structural change in work organization aims at increasing efficiency and in some cases, economy, too. The authors used qualitative and quantitative approach based on original survey data from own research, including data collected within the LIPSE project. Main findings point out the factors that influence the use of telework in the conditions of Slovakia in a selected public sector organization, e.g. the social, technological and inter-institutional dynamics factors playing a vital role in telework adoption.